Keabsahan Force Majeure Dalam Perjanjian Di Masa Era Pandemi Covid-19 - Bambang Eko Muljono; Dhevi Nayasari Sastradinata (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
In connection with the failure to fulfill an obligation of one of the parties due to force majeure or coercive circumstances, this can happen if there is an event that occurs beyond human control in order to avoid such an event. The consequence of this force majeure is that an agreement can be canceled or delayed or even canceled by law, because one of the parties does not carry out its obligations due to its inability to fulfill its obligations because it is in a state of compulsion. As is currently happening, the existence of the Covid-19 pandemic as a type of infectious disease that causes an emergency for the health of the entire community, has made the Indonesian Government determine that the Covid-19 pandemic is a national disaster. This has led to a government policy for people to carry out social distancing or to maintain distance between people and even work and study must also be done from home. This is of course very influential on the decline in economic income. The economic needs of the community that should be fulfilled for their survival. In fact, there are also many people who are required to pay installments according to a previously agreed period of time to carry out the aims and objectives of an agreement. This of course will be very burdensome to the people who have the responsibility to pay these installments.